A maxillary reconstruction after osteonecrosis with surgical biomodels: A case report - Helena Polmann; Beatriz Helena Eger Schmitt; Roberta Aliny Santos Bendini; Pablo Cornelius Comelli Leite (Elsevier, 2021)
Medication-related osteonecrosis of the jaw is a low prevalence condition in cancer patients which is mainly associated with bisphosphonates and other medication therapies, such as antiresorptive and antiangiogenic therapies. The aim of this paper is to report a severe and rare case of the condition in a 64 years-old edentulous man who has been treated with bisphosphonates and angiogenic medication for a prostate cancer. Treatment involved a total maxillectomy with immediate reconstruction with a customized infra structure of titanium implant for prosthetic rehabilitation of the upper arch dentition aimed to keep the masticatory function. This protocol allowed immediate reestablishment of the masticatory function in cancer patient under bisphosphonates and angiogenic medication which is fundamental for the general health of the patient.